Employee Suggestion System as An Effective Tool of Engaging Employees in Implementing Lean Management Concepts - Damian OSTROWSKI; Przemysław WIT (Communications of International Proceedings, 2022)
The Lean Management concept is made up of two layers: a theoretical one which presents the basic assumptions related to values, birth history, assumptions, etc., and a practical one describing the tools implemented in business practice to realise the theoretical foundations. The concept of Lean Management contains a multitude of tools and can be divided into many types, characteristics, etc. One of the most frequently implemented tools involves an employee suggestion system, which, when properly implemented and managed, can bring great benefits in material terms (reducing the organisation's operating costs) and in immaterial terms (increasing employee involvement, taking the initiative by lower-level staff, employee participation, etc.). In this paper, the authors present a practical example of how this tool works in one of the enterprises located in the Lower Silesian region. Based on a research survey, the authors assess the effectiveness of this tool from the employees' perspective. Questions in the research survey addressed, inter alia, the following issues: factors influencing the effective operation of the employee suggestion system, types of employee ideas, the way in which management involves employees in submitting ideas, barriers and motivation. The paper concludes relevant summaries and suggestions for improving the operation of this tool in practice. In the theoretical part, the authors present a brief historical outline of the employee suggestion system defining its basic features and principles of implementation.
Keywords: lean management; employee suggestion system